DAYA HASIL DAN MUTU FISIOLOGISBENIH EMPAT VARIETAS SORGUM MANIS (Sorghum bicolor (L.)Moench)YANG DIBERI BERBAGAI DOSIS PUPUK KALIUM - Lian Syah Putra; Nurbaiti Nurbaiti; Elza Zuhry (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this study was to determine the yield and quality of seeds of four varieties of sweet sorghum were given different doses of potassium fertilizers as well as to get a dose of potassium is best to yield and seed quality of sweet sorghum. This research was carried out in the field and laboratory experiments Plant Breeding, Faculty of Agriculture, University of Riau, from August 2014 to December 2014. This study was conducted using a randomized block design (RAK) arranged as factorial with two factors and three replications. The first factor is composed of four varieties of sorghum varieties that Kawali, Numbu, sculpting and Mandau. Factor II is a dose of KCl fertilizer consists of three levels IE: 30 kg KCl / ha, 60 kg KCl / ha and 90 kg KCl / ha. The parameters observed where grain weight / panicle, weight of 1000 seeds, seed weight / m2, moisture content, germination test, first count test, test speed germination, seedling dry weight, test plumula and radicle growth. Data was analyzed with Anova and Duncan's multiple range test level of 5%. The results showed that 60 kg / ha KCl produced the highest yield on Kawali varieties as many as 11.2 tons / ha. KCl fertilizer application as much as 30 kg / ha gave the best seed physiological quality for varieties Kawali, Numbu, and Mandau. Keywords:sorghum, potassium, yield, physiological seed quality